ANALISIS PENGARUH PERMAINAN GASING MELAYU TERHADAP PEMBELAJARAN TEKS PROSEDUR KELAS 9 SMP NEGERI 5 TANJUNGPINANG - Rizka Annisa Destiana; Siswandi; Wan Faridah; Maulida Mustado; Denti Afrita (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of using the traditional Malay spinning top (Gasing Melayu) as an instructional medium on students’ understanding of procedural text writing in Grade IX at SMP 5. This research employs a descriptive qualitative method through classroom observations, interviews, and analysis of students’ written tasks. The findings indicate that the use of gasing Melayu enhances students’ learning motivation, facilitates their understanding of the structure of procedural texts, and helps them write step-by-step procedures more coherently and logically. The integration of this local cultural game is considered effective in creating an engaging and meaningful learning experience.